What's your opinion? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Do you have ideas and experiences concerning the development of information and communication technologies (ICTs) in African agriculture and natural resource management (NRM)? You might want to share these or exchange ideas with others through the...